Knowledge, attitudes and practices among healthcare professionals regarding complementary alternative medicine use by patients with hypertension and type 2 diabetes mellitus in Western Jamaica - Grace Kwak; Kimberly Gardner; Bolanle Bolaji; Sarah Franklin; Maung Aung; Pauline E. Jolly (Elsevier, 2021)
Objectives: This study investigated the knowledge, attitudes, and practices (KAP) of healthcare professionals (HCPs) regarding CAM use for Hypertension (HTN) and Type 2 Diabetes Mellitus (T2DM) among patients in western Jamaica, and to determine HCPs' perceptions of the need for training on CAM. Design: A cross-sectional study was conducted from May to August 2019. Setting: HCPs serving patients with HTN and T2DM in chronic disease clinics in western Jamaica completed a self-administered questionnaire that provided data on their sociodemographic characteristics, training, and KAP of CAM. Main outcome measure: The data identified factors associated with discussion and recommendation of CAM to patients and personal use of CAM by HCPs. Results: Type of profession (physicians vs nurses OR = 2.17; 95 % CI = 1.07−4.42 and pharmacists vs nurses OR = 8.67; 95 % CI = 2.83−26.57) was significantly associated with discussion of CAM. Training on CAM was significantly associated with discussion (OR = 2.36; 95 % CI = 1.26−4.42), recommendation (OR = 2.72; 95 % CI = 1.36-5.42), and personal use of CAM (OR = 2.90; 95 % CI = 1.69−4.97). Dieticians and nutritionists had 4.56 higher odds of personal use of CAM (95 % CI = 1.16−17.86), and personal use of CAM was significantly associated with discussion (OR = 8.94; 95 % CI = 4.76−16.80) and recommendation (OR = 7.17; 95 % CI = 3.54-14.51) of CAM. The majority of HCPs (70-89 %) agreed that there is a need to include CAM in professional training programs. Conclusion: The results of this study can be used to guide development of programs for training HCPs on knowledge and safe use of CAM so that they can better serve their patients.